2023
DOI: 10.1038/s41598-023-34939-6
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of factors affecting nonunion by radiographic analysis after intramedullary nailing in segmental femoral shaft fractures

Abstract: The factors affecting the outcomes of segmental femoral shaft fractures are currently unknown. We evaluated the outcomes of intramedullary (IM) nail fixation and investigated factors affecting nonunion of femoral shaft segmental fractures. A total of 38 patients who underwent IM nail fixation for femoral shaft segmental fractures (AO/OTA 32C2) at three university hospitals with a minimum 1-year follow-up period were retrospectively reviewed. The patients were divided into union (n = 32) and nonunion (n = 6) gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Kempf et al 29 , Wiss et al 30 and Karadimas et al 3 reported non-union rates of 10% (5/52), 2% (1/33) and 3.8% (5/131), respectively. Recently, Kook et al 31 reported a non-union rate of 15.8% (6/38) for intact segmental femoral shaft fractures treated with intra-medullary nail fixation (AO/OTA 32C2). The findings of those researches are relatively lower than what we have observed.…”
Section: Discussionmentioning
confidence: 99%
“…Kempf et al 29 , Wiss et al 30 and Karadimas et al 3 reported non-union rates of 10% (5/52), 2% (1/33) and 3.8% (5/131), respectively. Recently, Kook et al 31 reported a non-union rate of 15.8% (6/38) for intact segmental femoral shaft fractures treated with intra-medullary nail fixation (AO/OTA 32C2). The findings of those researches are relatively lower than what we have observed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for femoral shaft fractures, two recent studies have described non-union rates ranging from 5.8% for patients from a single Level 1 trauma center treated with intramedullary nails [ 18 ] to 15.8% for patients from multiple sites with segmental shaft fractures [ 19 ]. In our study, femoral shaft fractures had a risk of non-union of 9.0% (7.8%–10.2%).…”
Section: Discussionmentioning
confidence: 99%
“…For patients younger than 65 years with femoral neck fractures, the preferred treatment methods are closed reduction internal fixation and femoral head preservation [ 2 , 3 ]. Displacement and inadequate reduction of fractures significantly contribute to nonunion [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%